Time-dependent deformation of Wufeng-Longmaxi shale and its implications on the in situ state of stress - Cheng, Wei; Zhang, Xiaowen; Jin, Juan; Liu, Jiandong; Jiang, Weidong; Zhang, Guangming; Zhang, Shihuai; Ma, Xiaodong (Frontiers in Earth Science, 2023)
The stress-strain relationship in shales is generally time-dependent. This concerns their long-term deformation in unconventional reservoirs, and its influence on the in situ stress state therein. This paper presents an experimental investigation on the time-dependent deformation of the Longmaxi shale gas shale. A series of creep experiments subject the shale samples to long-term, multi-step triaxial compression. It is found that the shale samples exhibit varying degrees of time-dependent deformation, which can be adequately described by a power-law function of time. The experimental results establish the relationship between the elastic Young’s modulus and viscoplastic constitutive parameters, which are different from previous those derived from North American shales. Based on this viscoplastic constitutive model, the stress relaxation and the differential stress accumulation over geologic time scales can be estimated. It is found that linear elasticity substantially overestimates the differential stress accumulation predicted in the context of viscoplastic relaxation. The characterized viscoplasticity and stress relaxation are of vital importance for various geomechanical problems in shale reservoirs.